المسؤولية الاجتماعية وأثرها على الموارد البشرية في منظمات الأعمال - شقراني، محمد; هزرشي، طارق (المركز الجامعي أحمد بن يحي الونشريسي تيسمسيلت, 2016)
This study deals with the subject of social responsibility and its relationship to human resources in business organizations and yield benefits from exercise there is a growing sense that business organizations have become in their activities less commitment to their social responsibilities which reveals the real need to need to adopt especially with regard to human resources and dealing this responsibility with the organization whether inside or outside of the surrounding environment and for the duration of her life as it is the heartbeat of the organization in addition to these organizations now see that poor social act could be of a very high cost to the organization and the community as a whole.
تتناول هذه الدراسة موضوع المسؤولية الاجتماعية وعلاقتها بالموارد البشرية في منظمات الأعمال والفوائد المتربة عن ممارستها، فهناك إحساس متزايد بأن منظمات الأعمال أصبحت في نشاطاتها أقل التزام بمسؤولياتها الاجتماعية، مما يكشف عن الحاجة الحقيقية إلى ضرورة تبني هذه المسؤولية خاصة فيما يتعلق بالموارد البشرية والتي تتعامل معها المنظمة سواء داخل أو خارج البيئة المحيطة بها وطيلة فترة حياتها فهي بمثابة القلب النابض للمنظمة، بالإضافة أن هذه المنظمات ترى الآن أن سوء التصرف الاجتماعي يمكن أن يكون ذا تكلفة عالية جدا على المنظمة والمجتمع برمته.
Keywords: المسؤولية الاجتماعية -- الموارد البشرية -- منظمات الأعمال -- الثقافة التنظيمية